EFFECT OF QUENCHING MEDIA VARIATIONS ON THE HARDNESS AND MICROSTRUCTURES OF AISI O1 TOOL STEEL - Hariningsih -; Desi Gustiani; Sutiyoko - (Media Mesin: Majalah Teknik Mesin, 2023)
Tool steels AISI O1 are widely used in the manufacturing industry to produce a wide variety of tools, moulds, and other applications requiring high wear resistance. Wear resistance is identic with high hardness, and the combination can be obtained by hardening-tempering and cryogenic treatment. However, cryogenic treatment requires liquid nitrogen, which is relatively expensive. Therefore, this study aims to determine whether to cool to produce high hardness, which is close to the hardness value of 69 HRC due to cryogenic treatment. The hardening process was carried out by heating the steel at a temperature of 880 °C and holding it for 30 minutes, then quenching using air, oil SAE 10, water with 15% salt, and ice water. The microstructure of the test sample was observed with an optical microscope, and the hardness was tested with a Rockwell hardness tester. The test results showed that the microstructure changed from pearlite and ferrite to bainite and martensite after hardening-quenching. The lower the quenching media temperature, the higher the hardness. Ice water quenching resulted in a fully martensitic structure, and the highest hardness was 66.37 HRC. Ice water is a quenching medium that can produce hardness almost close to the hardness of cryogenic treatment.